Peran Orang Tua Terkait Pendidikan Seks Untuk Anak Usia Dini - Nursabrina, Zata Yumni Subhati; Mukhlis, Imam (CV. Lenggogeni Data Publishing, 2024)
The level of sexual violence in Indonesia still tends to increase every year. Recorded in 2023 as many as 11,302 cases of sexual crimes and 315 child exploitation. This data indicates that cases of sexual violence are still commonplace and cannot be overcome especially with minor victims. The role of parents is needed in providing education to children by building good communication between children and parents and parents provide an understanding of sex and must be done gradually according to the development of the child. The purpose of this study is to explore the role of parents regarding sex education in minors. This research design is qualitative research using a phenomenological approach that produces descriptive data. Based on the results of the study, it shows that the perpetrators do not have good knowledge with a low educational background. The perpetrators have a positive attitude towards the actions taken, so that the perpetrators do not feel guilty in committing acts of sexual violence against children. Interaction between children and parents at home is still rarely done due to their busy schedules so that children do not get enough education about sex education. Keywords: , ,